Method for catalyzing rapid spontaneous combustion of N (CN) 2-IL-H2O2 system by twin-crystal Cu NPs

By using twin Cu NPs catalysts to catalyze the N(CN)2-IL-H2O2 system, the problem of existing IL-H2O2 propellants not spontaneously ignition is solved, rapid spontaneous ignition and low ignition delay time are achieved, and it has important industrial application value.

CN119841699APending Publication Date: 2025-04-18HENAN UNIVERSITY +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510049271.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing IL-H2O2 propellant system has weak acidity and high latent heat, which causes most ionic liquids to not spontaneously ignite with H2O2, limiting the application of IL-H2O2.

Method used

Using twin Cu NPs catalyst, the mixing of twin Cu NPs with N(CN)2-ionic liquid is used to form a mixed fuel and drip it into an oxidant cell containing H2O2 to achieve rapid spontaneous combustion of the N(CN)2-IL-H2O2 system.

Benefits of technology

The spontaneous combustion performance of N(CN)2-IL and H2O2 is significantly improved, and the ignition delay time is as low as 25 ms. It is simple to operate and fast reaction, and has high industrial application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841699A_ABST
    Figure CN119841699A_ABST
Patent Text Reader

Abstract

The invention provides a method for catalyzing rapid spontaneous combustion of an N (CN) 2-IL-H2O2 system by twin-crystal Cu NPs, belongs to the field of rocket propellants, and aims to solve the problem that the N (CN) 2-IL-H2O2 system does not spontaneously ignite. The twin crystal Cu NPs and N (CN) 2-IL ionic liquid are mixed, the obtained mixed fuel is dropped into a cylindrical open glass bottle oxidant pool containing H2O2, and the ignition delay time is tested. The ignition process is recorded by a high-speed camera, and obtained data is an average value of three times of ignition tests. The spontaneous combustion performance of the N (CN) 2-IL-H2O2 system is reduced by utilizing the twin boundary defect of Cu NPs, and the ignition delay time is as low as 25 ms. The method is simple in operation and rapid in reaction, relatively low ignition delay time can be obtained, and accurate synthesis of the twin crystal Cu NPs is beneficial to industrial application of an N (CN) 2-IL-H2O2 propulsion system and rapid development of the aerospace industry in China.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of rocket propellant chemicals, and in particular relates to a twinned Cu NPs catalyzing N(CN)2 - Method for rapid spontaneous combustion of IL-H2O2 system. Background Art

[0002] As the power source of space launch, propellant drives space exploration towards faster, farther and larger payload. Compared with solid bipropellants, liquid bipropellants have high energy release efficiency: in liquid bipropellants, both fuel and oxidizer are in liquid state, and they can be fully mixed at the molecular level, burning more completely, with higher energy release efficiency. The specific impulse can generally reach 300-450 seconds, while the specific impulse of solid-liquid mixed propellants is usually around 250-350 seconds. Large thrust adjustment range: liquid bipropellants can flexibly change thrust within a large range by precisely adjusting flow rate, etc., and can meet the precise thrust requirements of spacecraft at different stages from launch to orbit. Solid-liquid mixed propellants are limited by the characteristics of solid fuels, and the thrust adjustment range is relatively narrow. Among them, the IL-H2O2 system is a very promising green bipropellant with hypergolic properties, which is expected to replace traditional propellant systems such as hydrazine-fuming nitric acid, which are highly toxic and corrosive. However, due to the weak acidity and high latent heat of H2O2, most ionic liquids such as BH-IL have a long ignition delay time with H2O2. - IL and H2O2 do not spontaneously ignite, which limits the application of IL-H2O2. Therefore, constructing a highly active catalyst IL-H2O2 that spontaneously ignites and significantly reduces the ignition delay time is of great significance to accelerate the industrial application of IL-H2O2.

[0003] The rapid self-ignition reaction of IL-H2O2 by catalysis is an efficient and convenient method. - IL is the most studied and widely used type of IL, but most of the current research is aimed at shortening the ignition delay time of BH-IL and H2O2, and few studies are on catalyzing the spontaneous combustion of N(CN)2-based IL-H2O2. In addition, most of the existing catalysts contain halogens, which is not conducive to the green development concept of propellants. The literature J. Mater. Chem. A, 2020, 8, 14661-14670 reported the use of [FcCH2N(CH3)3 + ]2[Cu2I4 2- ] and [FcCH2N(CH3)3 + ]n[Cu2I3 - ] nAs a catalyst, 1-ethyl-trimethylimidazolium dicyanamide ionic liquid ([EMIM][N(CN)2]) was catalyzed to react with 95% H2O2, and the ignition delay times were 54 ms and 42 ms, respectively. The literature Energetic Materials Frontiers 2024, 5, 41-46 reported that [EMIM][CuCl2] was used as a catalyst to catalyze the reaction of 1-ethyl-trimethylimidazolium dicyanamide ionic liquid ([EMIM][N(CN)2]) with 90% H2O2, and the ignition delay times were 36 ms, and [BMIM][CuCl2] was used as a catalyst to catalyze the reaction of 1-butyl-trimethylimidazolium dicyanamide ionic liquid ([BMIM][N(CN)2]) with 90% H2O2, and the ignition delay times were 36 ms, respectively.

[0004] Defect engineering is one of the most effective modification methods for constructing the microstructure of micro / nano materials. The presence of appropriate crystal defects will destroy the periodicity of atomic arrangement and produce a certain amount of lattice distortion internal stress, which is conducive to regulating the crystal structure and electronic structure of the material, exposing more active sites, and thus improving its catalytic activity. Among them, twinning is the most stable defect. Twin boundaries can directly improve catalytic activity as active sites, and can also indirectly improve catalytic activity through strain effects caused by structural disturbances near twin boundaries. Introducing high-density twin interfaces in micro / nano metal catalysts is one of the effective methods to optimize the microstructure of the catalyst surface and prepare highly active catalysts. Compared with other catalysts, metal nanoparticle catalysts have high atomic utilization and more catalytic active sites. Using the same amount of catalyst can achieve better catalytic effects. Summary of the invention

[0005] Targeting N(CN)2 - The present invention proposes a twinned Cu NPs catalyzed N(CN)2 - The method for rapid spontaneous combustion of the IL-H2O2 system has the advantages of high selectivity, high atom economy, mild reaction conditions, and short ignition delay time.

[0006] In order to achieve the above object, the technical solution of the present invention is achieved as follows: A twinned Cu NPs catalyzes N(CN)2 - The method for rapid spontaneous combustion of an IL-H2O2 system comprises the following steps: mixing a twinned Cu NPs catalyst and N(CN)2 - The ionic liquids were mixed to obtain a mixed fuel, which was then dropped into an open cylindrical glass bottle oxidant pool containing H2O2 to test the ignition delay time. The ignition process was recorded using a high-speed camera, and the data obtained was the average of three ignition tests.

[0007] Furthermore, the amount of twinned Cu NPs catalyst in the mixed fuel is 5-15 wt%, N(CN)2 - The dosage of IL is 95-85wt%, and the mass concentration of H2O2 in the oxidant pool is 90-98%.

[0008] Further, the N(CN)2 - IL is one or more of 1-butyl-trimethylimidazolium dicyanamide ionic liquid, 1-ethyl-trimethylimidazolium dicyanamide ionic liquid or 1-allyl-trimethylimidazolium dicyanamide ionic liquid.

[0009] Further, the volume of H2O2 in the oxidant tank is 15 mL, and the volume of the mixed fuel dropped into the oxidant tank is 15 μL.

[0010] Furthermore, twinned Cu NPs catalyzed N(CN)2 - The ignition delay time of the IL-H2O2 system for rapid self-ignition is as low as 25ms.

[0011] Furthermore, the preparation method of the twinned Cu NPs catalyst is: sodium carbonate, sodium citrate, copper salt, sodium chloride, and glucose solution are mixed, fully stirred, heated for reaction, and centrifuged, washed, and dried to obtain the twinned Cu NPs catalyst.

[0012] Further, the copper salt is one or more of copper sulfate, copper acetate, copper nitrate, and copper chloride, and the solvent is deionized water, methanol, ethanol, dichloromethane, acetonitrile or N, N - one or more of dimethylformamide.

[0013] Furthermore, the molar ratio of the sodium carbonate, sodium citrate, copper salt, sodium chloride and glucose solution is 70:20:3:50:45.

[0014] Furthermore, the heating reaction temperature is 50-200°C and the time is 1-8h.

[0015] Furthermore, the particle size of the twinned Cu NPs catalyst is about 300 nm, and the microscopic morphology is spherical nanoparticles with dislocations, stacking faults, and twin defects on the surface.

[0016] Furthermore, the container for preparing the twinned Cu NPs catalyst is a round-bottom flask or a high-pressure reactor.

[0017] Beneficial effects of the present invention: The present invention uses twinned Cu NPs to significantly increase N(CN)2 -The self-ignition performance of IL with H2O2 is as low as 25 ms, which is mainly attributed to the twin boundaries on the surface of Cu NPs, which reduce the band gap between the d-band center and the Fermi level, facilitate the electron transfer from the d electrons of Cu atoms to the antibonding orbital of H2O2, effectively activate the OO bond in H2O2, and produce ·OH and ·OOH with stronger oxidation activity, thus achieving the reaction with N(CN)2 - In addition, the present invention is simple to operate, has a fast reaction, and can obtain a lower ignition delay time. The precise synthesis of twinned Cu NPs helps N(CN)2 - The industrial application of IL-H2O2 propulsion system and the rapid development of my country's aerospace industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 This is the color change diagram of the solution for preparing twinned Cu NPs. Figure 2 is the microscopic morphology of twinned Cu NPs.

[0020] Figure 3 Cu NPs catalyze N(CN)2 - Schematic diagram of ignition of IL-H2O2 system.

[0021] Figure 4 The catalytic activity of twinned Cu NPs (a) and ordinary Cu NPs (b) in N(CN)2 - Ignition diagram of IL-H2O2 system.

[0022] Figure 5 It is the projected density of states (DOS) diagram of twinned Cu NPs and ordinary Cu NPs. DETAILED DESCRIPTION

[0023] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The Cu NPs material of the present invention can be used as a self-ignition catalyst to reduce the ignition delay time of self-ignition propellants, and is expected to be applied to liquid bi-component rocket engines to improve the engine ignition stability. At the same time, Cu NPs can greatly improve the ignition performance of ionic liquids, laying a foundation for the practical application of ionic liquids-H2O2.

[0025] The preparation method of the Cu NPs catalyst in the following embodiment is: sodium carbonate, sodium citrate, copper salt, sodium chloride, and glucose solution are mixed, stirred sufficiently, heated for reaction, centrifuged, washed, and dried to obtain a twinned Cu NPs catalyst. The defects of the CuNPs catalyst are regulated by the synthesis method.

[0026] Example 1 A method for preparing a twinned Cu NPs catalyst, the color change of the solution when preparing the twinned Cu NPs is shown in the figure Figure 1 As shown, the following steps are included: Na2CO3 (7mmol, 0.7419g) is added to 10 ml of water and stirred thoroughly to dissolve. Then Na3C6H5O7·2H2O (2mmol, 0.5880g) is added to the above solution and stirred thoroughly. Then 4 mL of CuSO4 (68 mM) aqueous solution is added dropwise to the above mixture. The solution changes from colorless to dark blue and continues to stir. Add NaCl (5 mmol, 0.2922 g) to the dark blue mixed solution and stir until dissolved. Finally, add 30 mL of d-glucose solution (150mM) to the mixed solution and stir thoroughly. Transfer the above dark blue mixture to a high pressure reactor and react at 150°C for 6 hours.

[0027] The solution color gradually changed from dark blue to green, then to orange, and finally to a reddish brown mixture. After cooling to room temperature, centrifugation was performed, and the solid was washed three times with deionized water and filtered to obtain a reddish brown solid, which was vacuum dried at 60°C for 12 h to obtain a twinned Cu NPs catalyst.

[0028] Example 2 The reaction steps of Example 2 are the same as those of Example 1, except that the reaction conditions include: the reaction vessel is a round-bottom flask, the reaction temperature is 100° C., and the reaction time is 2 h.

[0029] Example 3 In this example, twinned Cu NPs catalyze N(CN)2 - The method for rapid spontaneous combustion of the IL-H2O2 system is as follows: The twinned Cu NPs catalyst prepared in Example 1 was mixed with [BMIM]N(CN)2IL, wherein the mass fraction of Cu NPs was 1wt%. The obtained mixed fuel was ultrasonicated at 25°C and 300W for 30min to fully disperse the Cu NPs in [BMIM]N(CN)2IL. A 15 mL cylindrical open glass bottle was filled with 1.5 mL of 98% H2O2 as an oxidant pool, and 50 μL of the twinned Cu NPs and [BMIM]N(CN)2 mixed fuel was dropped into the oxidant pool. The ignition process was recorded using a high-speed camera at 5000 frames / s −1 The speed was recorded and the data obtained was the average value of three ignition tests. The results showed that 1wt% twinned CuNPs could not cause the [BMIM]N(CN)2-H2O2 system to spontaneously ignite, but only slightly bubbled.

[0030] Example 4 In this example, twinned Cu NPs catalyze N(CN)2 - The method for rapid spontaneous combustion of the IL-H2O2 system is as follows: The twinned Cu NPs catalyst prepared in Example 1 was mixed with [BMIM]N(CN)2IL, wherein the mass fraction of Cu NPs was 5wt%. The obtained mixed fuel was ultrasonicated at 25°C and 300W for 30min to fully disperse the Cu NPs in [BMIM]N(CN)2IL. A 15 mL cylindrical open glass bottle was filled with 1.5 mL of 98% H2O2 as an oxidant pool, and 50 μL of the twinned Cu NPs and [BMIM]N(CN)2 mixed fuel was dropped into the oxidant pool. The ignition process was recorded using a high-speed camera at 5000 frames / s −1 The speed was recorded and the data obtained was the average of three ignition tests. The results showed that the ignition delay time of spontaneous combustion of [BMIM]N(CN)2-H2O2 system catalyzed by 5wt% twinned CuNPs was 65ms.

[0031] Example 5 In this example, twinned Cu NPs catalyze N(CN)2 - The method for rapid spontaneous combustion of the IL-H2O2 system is as follows: The twinned Cu NPs catalyst prepared in Example 1 was mixed with [BMIM]N(CN)2IL, wherein the mass fraction of Cu NPs was 10wt%. The obtained mixed fuel was ultrasonicated at 25°C and 300W for 30min to fully disperse the Cu NPs in [BMIM]N(CN)2IL. A 15 mL cylindrical open glass bottle was filled with 1.5 mL of 98% H2O2 as an oxidant pool, and 50 μL of the twinned Cu NPs and [BMIM]N(CN)2 mixed fuel was dropped into the oxidant pool. The ignition process was recorded using a high-speed camera at 5000 frames / s −1 The speed was recorded and the data obtained was the average of three ignition tests. The results showed that the ignition delay time of spontaneous combustion of [BMIM]N(CN)2-H2O2 system catalyzed by 10wt% twinned Cu NPs was 25ms.

[0032] Example 6 In this example, twinned Cu NPs catalyze N(CN)2 - The method for rapid spontaneous combustion of the IL-H2O2 system is as follows: The twinned Cu NPs catalyst prepared in Example 1 was mixed with [BMIM]N(CN)2IL, wherein the mass fraction of Cu NPs was 15wt%. The obtained mixed fuel was ultrasonicated at 25°C and 300W for 30min to fully disperse the Cu NPs in [BMIM]N(CN)2IL. A 15 mL cylindrical open glass bottle was filled with 1.5 mL of 98% H2O2 as an oxidant pool, and 50 μL of the twinned Cu NPs and [BMIM]N(CN)2 mixed fuel was dropped into the oxidant pool. The ignition process was recorded using a high-speed camera at 5000 frames / s −1 The speed was recorded and the data obtained was the average of three ignition tests. The results showed that the ignition delay time of spontaneous combustion of [BMIM]N(CN)2-H2O2 system catalyzed by 15wt% twinned Cu NPs was 43ms.

[0033] Comparative Example 1 In order to compare the catalytic effect of twinned Cu NPs catalyst, a comparative experiment without catalyst was carried out. At room temperature, a 15 mL cylindrical open glass bottle was filled with 1.5 mL of 98% H2O2 as the oxidant pool, and 50 μL of [BMIM]N(CN)2 mixed fuel was dropped into the oxidant pool. The ignition process was recorded with a high-speed camera at 5000 frames / s −1 The speed was recorded and the data obtained was the average value of three ignition tests. The results showed that the [BMIM]N(CN)2-H2O2 system did not spontaneously ignite.

[0034] Comparative Example 2 In order to compare the catalytic effect of twinned Cu NPs catalyst, a comparative experiment of ordinary Cu NPs catalyst (without dislocation, stacking fault, twinning and other defects) was carried out. Ordinary Cu NPs were mixed with [BMIM]N(CN)2IL, where the mass fraction of ordinary Cu NPs was 1wt%. The obtained mixed fuel was ultrasonicated at 25℃ and 300W for 30min to fully disperse Cu NPs in [BMIM]N(CN)2IL. A 15 mL cylindrical open glass bottle was used to hold 1.5 mL of 98% H2O2 as the oxidant pool, and 50 μL of the mixed fuel of ordinary Cu NPs and [BMIM]N(CN)2 was dropped into the oxidant pool. The ignition process was recorded using a high-speed camera at 5000 frames·s −1 The speed was recorded and the data obtained was the average value of three ignition tests. The results showed that 1wt% ordinary CuNPs could not catalyze the spontaneous combustion of the [BMIM]N(CN)2-H2O2 system.

[0035] Comparative Example 3 In order to compare the catalytic effect of twinned Cu NPs catalyst, a comparative experiment of ordinary Cu NPs catalyst (without dislocation, stacking fault, twinning and other defects) was carried out. Ordinary Cu NPs were mixed with [BMIM]N(CN)2IL, where the mass fraction of ordinary Cu NPs was 5wt%. The obtained mixed fuel was ultrasonicated at 25℃ and 300W for 30min to fully disperse Cu NPs in [BMIM]N(CN)2IL. A 15 mL cylindrical open glass bottle was used to hold 1.5 mL of 98% H2O2 as the oxidant pool, and 50 μL of ordinary Cu NPs and [BMIM]N(CN)2 mixed fuel was dropped into the oxidant pool. The ignition process was recorded using a high-speed camera at 5000 frames·s −1 The speed was recorded and the data obtained was the average of three ignition tests. The results showed that the ignition delay time of spontaneous combustion of [BMIM]N(CN)2-H2O2 system catalyzed by 5wt% ordinary CuNPs was 94ms.

[0036] Comparative Example 4 In order to compare the catalytic effect of twinned Cu NPs catalyst, a comparative experiment of ordinary Cu NPs catalyst (without dislocation, stacking fault, twinning and other defects) was carried out. Ordinary Cu NPs were mixed with [BMIM]N(CN)2IL, where the mass fraction of ordinary Cu NPs was 10wt%. The obtained mixed fuel was ultrasonicated at 25℃ and 300W for 30min to fully disperse Cu NPs in [BMIM]N(CN)2IL. A 15 mL cylindrical open glass bottle was used to hold 1.5 mL of 98% H2O2 as the oxidant pool, and 50 μL of the ordinary Cu NPs and [BMIM]N(CN)2 mixed fuel was dropped into the oxidant pool. The ignition process was recorded using a high-speed camera at 5000 frames·s −1 The speed was recorded and the data obtained was the average value of three ignition tests. The results showed that the ignition delay time of spontaneous combustion of [BMIM]N(CN)2-H2O2 system catalyzed by 10wt% ordinary CuNPs was 55ms.

[0037] Comparative Example 5 In order to compare the catalytic effect of twinned Cu NPs catalyst, a comparative experiment of ordinary Cu NPs catalyst (without dislocation, stacking fault, twinning and other defects) was carried out. Ordinary Cu NPs were mixed with [BMIM]N(CN)2IL, where the mass fraction of ordinary Cu NPs was 15wt%. The obtained mixed fuel was ultrasonicated at 25℃ and 300W for 30min to fully disperse Cu NPs in [BMIM]N(CN)2IL. A 15 mL cylindrical open glass bottle was used to hold 1.5 mL of 98% H2O2 as the oxidant pool, and 50 μL of the ordinary Cu NPs and [BMIM]N(CN)2 mixed fuel was dropped into the oxidant pool. The ignition process was recorded using a high-speed camera at 5000 frames·s −1 The speed was recorded and the data obtained was the average of three ignition tests. The results showed that the ignition delay time of spontaneous combustion of the [BMIM]N(CN)2-H2O2 system catalyzed by 15wt% ordinary CuNPs was 76ms.

[0038] The microscopic morphology of the twinned Cu NPs prepared in Example 1 is shown in FIG. Figure 2 As shown, from Figure 2 a Stacking faults can be observed. Figure 2 b A large number of dislocations can be observed, Figure 2 Amplification of c Figure 2 e The existence of twin boundaries can be observed. Figure 2 d shows that its lattice parameter is 0.2088 nm, corresponding to metal Cu 0 The ignition schematic diagrams of Example 3 and Comparative Example 4 are shown in FIG. Figure 3As shown, the ignition picture is as follows Figure 4 As shown in the data, under the condition of no catalyst, [BMIM]N(CN)2 and 98% H2O2 do not spontaneously ignite; under the condition of the same mass fraction of catalyst, the average ignition delay time of spontaneous combustion of [BMIM]N(CN)2- H2O2 system catalyzed by ordinary Cu NPs is longer than that of twinned Cu NPs, indicating that the twin boundaries in the twinned Cu NPs catalyst can significantly regulate the surface electronic state of CuNPs, thereby reducing the ignition delay time.

[0039] According to the DFT theory, the d-band centers of twinned Cu NPs and ordinary Cu NPs (see attached) were calculated using Gaussian16 software. Figure 5 ), Figure 4 It shows that the d-band center of ordinary Cu NPs is at -2.32eV, and the d-band center of twinned Cu NPs is at -2.08eV. The Dos of twinned Cu NPs is significantly shifted to the right, closer to the Fermi level. This means that the d→2π* electron transfer between twinned Cu NPs and H2O2 can occur more effectively, and can better adsorb and activate H2O2. This can further explain that the existence of twin boundaries regulates the electronic microenvironment of the catalyst surface. Twinned Cu NPs can more effectively catalyze the decomposition of H2O2 to produce ·OH and ·OOH, thereby achieving the purpose of rapid self-ignition with [BMIM]N(CN)2.

[0040] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A twinned Cu NPs catalyzes N(CN)2 - The method for rapid spontaneous combustion of IL-H2O2 system is characterized in that: The following steps are involved: The twinned Cu NPs catalyst and N(CN)2 - The ionic liquids were mixed to obtain a mixed fuel, which was then dropped into an open cylindrical glass bottle oxidant pool containing H2O2 to test the ignition delay time. The ignition process was recorded using a high-speed camera, and the data obtained was the average of three ignition tests.

2. The twinned Cu NPs according to claim 1 catalyze N(CN)2 - The method for rapid spontaneous combustion of IL-H2O2 system is characterized in that: The amount of twinned Cu NPs catalyst in the mixed fuel is 5-15 wt%, N(CN)2 - The dosage of IL is 95-85wt%, and the mass concentration of H2O2 in the oxidant pool is 90-98%.

3. The twinned Cu NPs according to claim 1 catalyze N(CN)2 - The method for rapid spontaneous combustion of IL-H2O2 system is characterized in that: The N(CN)2 - IL is one or more of 1-butyl-trimethylimidazolium dicyanamide ionic liquid, 1-ethyl-trimethylimidazolium dicyanamide ionic liquid or 1-allyl-trimethylimidazolium dicyanamide ionic liquid.

4. The twinned Cu NPs according to claim 1 catalyze N(CN)2 - The method for rapid spontaneous combustion of IL-H2O2 system is characterized in that: The volume of H2O2 in the oxidant pool is 15 mL, and the volume of the mixed fuel dropped into the oxidant pool is 50 μL.

5. The twinned Cu NPs according to claim 1 catalyze N(CN)2 - The method for rapid spontaneous combustion of IL-H2O2 system is characterized in that: Twinned Cu NPs catalyze N(CN)2 - The ignition delay time of the IL-H2O2 system for rapid self-ignition is as low as 25 ms.

6. The twinned Cu NPs according to claim 1 catalyze N(CN)2 - The method for rapid spontaneous combustion of IL-H2O2 system is characterized in that: The preparation method of the twinned Cu NPs catalyst comprises the following steps: mixing sodium carbonate, sodium citrate, copper salt, sodium chloride and glucose solution, fully stirring, heating for reaction, and centrifugally separating, washing and drying to obtain the twinned Cu NPs catalyst.

7. The twinned Cu NPs according to claim 5 catalyze N(CN)2 - The method for rapid spontaneous combustion of IL-H2O2 system is characterized in that: The copper salt is one or more of copper sulfate, copper acetate, copper nitrate and copper chloride; the solvent is deionized water, methanol, ethanol, dichloromethane, acetonitrile or N, N - one or more of dimethylformamide.

8. The twinned Cu NPs according to claim 5 catalyze N(CN)2 - The method for rapid spontaneous combustion of IL-H2O2 system is characterized in that: The molar ratio of the sodium carbonate, sodium citrate, copper salt, sodium chloride and glucose solution is 70:20:3:50:

45.

9. The twinned Cu NPs according to claim 5 catalyze N(CN)2 - The method for rapid spontaneous combustion of IL-H2O2 system is characterized in that: The heating reaction temperature is 50-200°C and the time is 1-8h.

10. The twinned Cu NPs according to claim 5 catalyze N(CN)2 - The method for rapid spontaneous combustion of IL-H2O2 system is characterized in that: The twinned Cu NPs catalyst has a particle size of about 300 nm, a microscopic morphology of spherical nanoparticles, and dislocations, stacking faults, and twin defects on the surface.